Data pretreatment and multivariate analyses for ochre sourcing: Application to Leopard Cave (Erongo, Namibia). (February 2021) - Mauran, Guilhem; Caron, Benoît; Détroit, Florent; Nankela, Alma; Bahain, Jean-Jacques; Pleurdeau, David; Lebon, Matthieu
Highlights: Surveys in Central Namibia built a reference collection for potential ochre source. Micro-sample ICP-OES - ICP-MS/MS characterized archaeological and geological ochres. Multivariate analyses provided a sourcing model upholding the Provenance Postulate. Application to LSA Leopard Cave ochres revealed interactions among painters of rock art on different massifs. The ochre provenance model can be applied to other sites in Namibia. Abstract: Usually referred to as 'ochre' or 'pigment' in archaeological contexts, ferruginous rocks were commonly exploited during the Later Stone Age in southern Africa. While ochre could lead to crucial inferences about socio-cultural behaviours of past populations, the provenance and the procurement strategies of this material in LSA contexts, as well as its association to rock art remain largely understudied. In the present study, seventeen ochre sources from five geological zones in north-central Namibia and 41 archaeological ochre pieces discovered in the stratigraphic sequence of the Later Stone Age site of Leopard Cave, Erongo Mountains - Namibia, were analysed by ICP-OES and ICP-MS/MS. Geochemical data coupled to data pre-treatment considerations and multivariate statistical analyses demonstrate that archaeological ochres were both collected locally and regionally from more distant sources. Beyond shedding new light on ochre provenance for rock art in north-central Namibia during the Later Stone Age, our data provide new insight into the mobility of past populations and the interactions existing between distinct rock art areas in north-central Namibia.